Identification of TH Variants in Chinese Dopa-Responsive Dystonia Patients and Long-Term Outcomes - Li, Xin-yao; Yang, Ying-mai; Li, Li-bo; Zhang, Meng-yu; Huang, Yang-yu; Wang, Jie; Wang, Lin; Wan, Xin-hua (Frontiers in Neurology, 2021)
Background: Dopa-responsive dystonia (DRD) is a movement disorder that is highly clinically and genetically heterogeneous. Our study summarizes clinical characteristics and long-term outcomes in patients with dopa-responsive dystonia with the aim of obtaining further knowledge on this disorder. Methods: Patients who met DRD genetic diagnostic criteria through whole-exome sequencing and took levodopa for over 3 years were included in our study. Detailed information was collected on these patients, including family history, age at onset, age and dosage at starting levodopa, current medication and dosage, levodopa duration, diurnal fluctuation and other clinical features. Burke-Fahn-Marsden Dystonia Rating Scale-Motor (BFMDRS-M) score was used to evaluate patients’ dystonia and variation after levodopa. According to the long-term outcomes, patients were further graded as good (dystonia improved by more than 50% after levodopa, and no further motor symptoms appeared) and poor (dystonia improved by less than 50% after levodopa, or new motor symptoms appeared). Results: A total of 20 DRD patients were included (11 with GCH1 variants, 9 with TH variants). During long-term levodopa treatment, three patients with TH variants (3/20, 15%) developed motor symptoms, including body jerks and paroxysmal symptoms, and responded well to increasing levodopa doses. The patient with homozygous mutation c.1481C>T/p. Thr494Met harbored more serious symptoms and poor response to levodopa and showed decreased cardiac uptake in MIBG. Conclusions: Most DRD patients showed satisfactory treatment outcomes after long- term levodopa, whereas few patients with TH variants presented motor symptoms, which is considered to be related to dopamine insufficiency. For patients with motor symptoms after long-term levodopa, increasing the dose slowly might be helpful to relieve symptoms.